2010
DOI: 10.1088/0953-4075/43/11/115201
|View full text |Cite
|
Sign up to set email alerts
|

An extended empirical formula for inner-shell ionization of atoms

Abstract: An extension of the analytical model of Campos et al (2007 J. Phys. B: At. Mol. Opt. Phys. 40 3835) is proposed to evaluate electron impact single inner-shell ionization cross sections up to the M-shell. The new model includes ionic and relativistic factors in its structure and describes neatly the K-shell ionization cross section data up to 2 GeV, and L- and M-shell ionization data up to 300 MeV. Comparison is also made with other theoretical calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…A good agreement is also observed for the empirical models of Haque et al [21] and Hombourger [22]. Beyond the dip (ε > 10 MeV), the relativistic rise is steeper than in our model in both ab initio calculations (MRBEB and DWB/PWB) as well as in the fitted cross sections of Haque et al [21] and Hombourger [22]. Following the suggestion of Davies et al [1], the density-effect correction has been incorporated into the MRBEB model and the result is plotted in this figure.…”
Section: Calculationssupporting
confidence: 85%
See 2 more Smart Citations
“…A good agreement is also observed for the empirical models of Haque et al [21] and Hombourger [22]. Beyond the dip (ε > 10 MeV), the relativistic rise is steeper than in our model in both ab initio calculations (MRBEB and DWB/PWB) as well as in the fitted cross sections of Haque et al [21] and Hombourger [22]. Following the suggestion of Davies et al [1], the density-effect correction has been incorporated into the MRBEB model and the result is plotted in this figure.…”
Section: Calculationssupporting
confidence: 85%
“…the modified relativistic binary encounter Bethe (MRBEB) model of Guerra et al [11] and the combination of distorted-wave-Born and plane-wave-Born (DWB/PWB) models of Bote et al [20]. A good agreement is also observed for the empirical models of Haque et al [21] and Hombourger [22]. Beyond the dip (ε > 10 MeV), the relativistic rise is steeper than in our model in both ab initio calculations (MRBEB and DWB/PWB) as well as in the fitted cross sections of Haque et al [21] and Hombourger [22].…”
Section: Calculationsmentioning
confidence: 62%
See 1 more Smart Citation
“…1, our calculated K-shell EII cross sections in V 0 are compared to the experimental data compiled by Liu et al [35], the measurements of An et al [36], the empirical XCVTS formula of Haque et al [34], the combination of distorted-wave-Born and plane-wave-Born approximations (DWBA + PWBA) of Bote et al [33], the MRBEB model of Guerra et al [30] and this latter model corrected for the density effect as suggested by Davies et al [1] (MRBEB + Density Effects). Our RDW + Extrapol.…”
Section: Calculationsmentioning
confidence: 94%
“…The Vaisburd and Evdokimov [6], henceforth referred to as VE model, has the special feature in that it includes a special component describing the resonant ionization and joins elegantly with the Bethe formula valid at high-energy domain. The empirical formulae models proposed by Haque et al [7,8] provided successful description of cross-sections of electron impact inner-shell ionization of atoms for a wide range of atoms covering up to the energy of GeV order with inclusion of ionic and relativistic ingredients into the structures of the models .…”
Section: Introductionmentioning
confidence: 99%